Software Defined Optoelectronics: Space and Frequency Diversity in Heterodyne Interferometry - Riobó, Lucas Matías (2018)
In this paper, a general architecture for the implementation of software-defined optoelectronic systems is described. This concept harnesses the flexibility of software-defined hardware to implement optoelectronic systems which can be configured to adapt to multiple high speed optical engineering applications. As an application example, a software-defined optical interferometer using a commercial software-defined radio platform is built. The system is tested by performing high speed optical detection of laser-induced photoacoustic signals in a concentrated dye solution. Using software modifications only, conventional single carrier and also multicarrier heterodyne techniques with space and frequency diversity are performed. The latter technique shows a noticeable performance improvement in single-shot interferometric measurements.